Analisis Break Even Point Dan Faktor Yang Mempengaruhi Usaha Tahu Pada Masa Pandemi Covid-19 Di Kecamatan Tolangohula Kabupaten Gorontalo - Harija K. Mahalipa; Ria Indriani; Larasati Sukmadewi Wibowo; Supriyo Imran (Fapetrik-UMPAR, 2022)
This study aims to determine the break-even point and analyze the factors influencing tofu business income in Tolangohula District, Gorontalo Regency. This research approach uses quantitative methods. Methods of data collection using questionnaires/questionnaires and interview techniques. The results showed that the quantity in tofu production before the Covid-19 pandemic, when the break-even point began with the production BEP, acceptance BEP and price BEP were 34 boards, Rp. 1,187,552/month and Rp. 20,611/board. During the Covid-19 pandemic, when the production BEP break-even point, revenue BEP, and price BEP were 56 boards, Rp. 2,267,145/month and Rp. 31,518/board. Factors affecting the tofu business in Tolangohula District, Gorontalo Regency, have been tested simultaneously: labor, the selling price of tofu, production costs, and soybean production to income.